Wärmeübertrager auf der ACHEMA 2018. Issue 12 (25th September 2018) - Reiser, Sarah
Abstract: Heat transfer is omnipresent in the processes of the chemical industry. This was also reflected at the ACHEMA, where exhibitors on this topic could be found not only in the field of thermal processes, but also in the topics of plant construction, instrumentation and control techniques. An insight into the mood among the exhibitors as well as into current trends and challenges in the industry is given. The innovations in the areas of plate‐ and shell and tube heat exchangers, CFD simulation of heat exchangers and optimization of energy recovery are presented.